Features of gender, age, social factors and polymorbidity in patients, undergone COVID-19 - Yu. A. Nikolaev; E. V. Sevostyanova; I. M. Mitrofanov; V. Ya. Polyakov (Сибирский научный медицинский журнал, 2024)
Aim of the study was to identify the features of susceptibility to a new coronavirus infection СOVID-19 depending on gender, age, social factors and polymorbidity. Material and methods. An analysis of the structural features of gender, age, and social factors in 620 patients who underwent examination and treatment at the Federal Research Center of Fundamental and Translational Medicine clinic (Novosibirsk) was carried out. The patients were divided into 2 groups: the main group (group 2, age 56.4 ± 0.7 years) included 272 patients who underwent a new coronavirus infection COVID-19, confirmed by a positive PCR test or antibody testing, a comparison group (group 1, age 60.7 ± 0.7 years) – 348 people who did not have COVID-19 and were undergoing examination and treatment for chronic non-communicable diseases. Results. An analysis of the incidence of COVID-19 depending on gender showed that disease was more common, by 22 %, in women than in men. Patients who had COVID-19 were statistically significantly more likely (30%) to be in the second adult age period than those in the comparison group. When studying the social features of patients who underwent COVID-19, it was found that employees and employees of the administrative and managerial apparatus were significantly more likely to suffer from this infectious disease. An analysis of the structure of polymorbid pathology revealed that patients with COVID-19 had a significantly higher value of transsystemic polymorbidity.